Electrolyte additive, electrolyte and lithium ion battery
By adding fluoribene boric acid compounds and sulfate endone -type compounds to the electrolytes of lithium ion batteries, forming a CEI film with high LIF and libxoy content, and the distribution of LIF on the surface ladder of the positive electrode, solve the lithium -ion battery on the height The problem of expanding and cracking of the positive material under the voltage improves the cycle life of the battery and the ion transmission rate.
Patent Information
- Application Number
- CN202411721013.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-26
AI Technical Summary
At high voltage, the volume expansion of the positive electrode material of the lithium-ion battery leads to cracks, and the electrolyte solvent enters the positive electrode material, destroys the structure, and causes capacity attenuation. It is difficult for the prior art to form a high-strength CEI film to improve the cycle life.
By adding fluoriblybenzene boric acid compounds to the electrolyte as the first additive and sulfonate endone, it is used as the second additive, forming a tough CEI film with high LIF and libxoy content, and through controlling the content of the additive, LIF is in the content of the additive to make LIF be in The surface of the positive electrode is distributed in stairs, stabilizing the CEI film of the inner layer of the cathode.
It is possible to improve the cycle life of lithium-ion batteries under high voltage. By forming a stable CEI film, cracks and capacity attenuation of the cathode material are avoided, while the ion transmission rate is improved.
Smart Images

Figure BDA0005160643870000021 
Figure BDA0005160643870000022 
Figure BDA0005160643870000031
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrolyte additive, an electrolyte and a lithium-ion battery. Background Art
[0002] As the limiting voltage of positive electrode materials continues to increase (especially 4.3V+), the gram capacity of battery materials gradually increases, while the high-temperature performance of the battery deteriorates seriously and long cycle life cannot be guaranteed. Especially during long-term cyclic charge and discharge under high voltage, the volume of the positive electrode material will expand and cause serious cracks. The solvent in the electrolyte enters the interior of the positive electrode material, destroying the structure, and ultimately causing serious capacity decay problems.
[0003] In the related art, it is known that by covering the surface of the positive electrode material with a high-strength CEI film, cracks caused by volume changes can be suppressed or reversibly recovered, which will significantly improve the cycle life of the positive electrode even at a high cut-off voltage.
[0004] Therefore, how to form a high-strength CEI film to meet the requirements of high energy density of batteries is a research problem in the battery field. Summary of the invention
[0005] In order to solve or partially solve the problems existing in the related art, the present application provides an electrolyte additive, an electrolyte and a lithium ion battery, which can form a high LiF and LiB x O y The tough CEI film with high content and the generated LiF are distributed in a step-by-step manner on the surface of the positive electrode, which can ensure the relative stability of the CEI film in the inner layer of the cathode and improve the cycle life of the battery.
[0006] In a first aspect, the present application provides an electrolyte additive, including a first additive, wherein the first additive comprises a fluorophenylboric acid compound, and the mass percentage of the fluorophenylboric acid compound in the electrolyte is m 1 %,m 1 It is 0.5~10.
[0007] As an optional embodiment, the structural formula of the fluorophenylboronic acid compound is as follows:
[0008]
[0009] In structural formula 1, R1-R5 are each independently selected from one of C1-C10 alkanes, C1-C10 halogenated alkanes, fluorine atoms, cyano groups, and hydrogen atoms, and R1-R5 contain at least one fluorine atom; R6 and R7 are each independently selected from one of C1-C10 alkoxy groups, C1-C10 halogenated alkoxy groups, and hydroxy groups.
[0010] As an optional embodiment, the first additive comprises at least one of the following fluorophenylboronic acid compounds:
[0011]
[0012]
[0013] As an optional embodiment, the electrolyte additive further includes a second additive, and the second additive includes a sultone compound.
[0014] As an optional embodiment, the structural formula of the sultone compound is as follows:
[0015]
[0016] In structural formula 2, R8 and R9 are independently selected from one of C1-C10 saturated alkanes, halogen atoms, and hydrogen atoms; M and Q are selected from C and O, respectively.
[0017] As an optional embodiment, the second additive comprises at least one of the following sultone compounds:
[0018]
[0019] Compound 2-5.
[0020] As an optional embodiment, the amounts of the fluorophenylboronic acid compound and the sultone compound satisfy:
[0021] 2(m 1 +m 2 )≥A
[0022] Among them, the molar ratio of Ni element in the positive electrode active material is A, and the mass percentage of sultone compound in the electrolyte is m 2 %.
[0023] As a preferred embodiment, A is 1-9.
[0024] As a preferred embodiment, m 2 It is 1 to 10.
[0025] A second aspect of the present application provides an electrolyte comprising a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive comprises the electrolyte additive described above.
[0026] The third aspect of the present application provides a lithium-ion battery, a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is the electrolyte described above.
[0027] As an optional embodiment, the positive electrode active material of the positive electrode is selected from lithium cobalt oxide LiCoO 2 、Nickel manganese cobalt oxide lithium ternary material N a C b M c , LiFePO 4 , LiMn manganate 2 O 4 One or more of .
[0028] As a preferred embodiment, the positive electrode active material is selected from the nickel manganese cobalt lithium ternary material N a C b M c , and the nickel manganese cobalt lithium ternary material N a C b M c Chinese: a+b+c=10.
[0029] More preferably, a / (b+c)>1.
[0030] The technical solution provided by this application may have the following beneficial effects:
[0031] The fluorophenylboric acid compound contained in the first additive of the present application is a strong cathode ligand, which can effectively prevent the electrolyte from damaging the cathode material, and can participate in the formation of a high-toughness CEI film with a high content of LiF and LiBxOy. In addition, the present application controls the mass percentage of the fluorophenylboric acid compound in the electrolyte to be 0.5% to 10%, so that the LiF and LiBxOy content in the generated CEI film can be reduced. x O y The content of LiF and LiB in the inner and outer layers of the cathode surface is distributed in a stepped manner. This is because the formation of the CEI film is not only affected by the film-forming time of the inner and outer layers, but also related to the content of fluorophenylboronic acid compounds. On the one hand, the film-forming stage includes the inner layer film-forming stage and the outer layer film-forming stage. In the film-forming stage, the CEI film is first generated in the inner layer of the cathode, and the inner layer film-forming time is relatively short. Therefore, the LiF and LiB in the generated CEI film are x O y The content of LiF and LiB in the outer layer is relatively low; subsequently, as the chemical formation proceeds, the outer layer is continuously formed on the basis of the inner layer, and the outer layer takes a relatively long time to form, which will make the outer layer relative to the inner layer LiF and LiB x O y The content is higher, which results in the inner layer of LiF and LiB on the cathode surface. x O y The content of LiF and LiBxOy in the outer layer is small, and the content of LiF and LiBxOy in the outer layer is large. x O yA high content can prevent the inner CEI film from being damaged, improve the stability of the inner CEI, and thus increase the cycle life of the battery; on the other hand, if the content of fluorophenylboronic acid compounds is too low, they will be quickly consumed in the early stage of film formation (inner film formation stage), which may cause the LiF and LiB contained in the outer film to be x O y If the content of fluorophenylboric acid compounds is too high, the fluorophenylboric acid compounds at the cathode interface will be replenished too quickly, which may lead to excessive replenishment of fluorophenylboric acid compounds in the inner film-forming stage, which cannot be distinguished from the fluorophenylboric acid compounds replenished in the outer film-forming stage, making it difficult to form LiF and LiB in the CEI film. x O y Therefore, too high or too low a content is not conducive to the LiF and LiB x O y In addition, phenylboronic acid compounds can reduce the solvation effect between solvent and Li+, promote the desolvation effect of Li+, and improve the ion transfer rate.
[0032] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION
[0033] The embodiments of the present application will be described in more detail below. Although the embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0034] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0035] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0036] In the related art, it is known that by covering the surface of the positive electrode material with a high-strength CEI film, cracks caused by volume change can be suppressed or reversibly recovered, which will significantly improve the cycle life of the positive electrode even at a high cut-off voltage. Therefore, how to form a high-strength CEI film to meet the requirements of high energy density of batteries is a research problem in the battery field.
[0037] In view of the above problems, the present invention provides an electrolyte additive that can form a high LiF and LiB electrolyte at the positive electrode of the battery. x O y The tough CEI film with high content and the generated LiF are distributed in a step-by-step manner on the surface of the positive electrode, which can ensure the relative stability of the CEI film in the inner layer of the cathode and improve the cycle life of the battery.
[0038] The present application provides an electrolyte additive, including a first additive, wherein the first additive includes a fluorophenylboric acid compound, and the mass percentage of the fluorophenylboric acid compound in the electrolyte is m 1 %,m 1 It is 0.5~10.
[0039] The fluorophenylboric acid compound contained in the first additive in the embodiment of the present application is a strong cathode ligand, which can effectively prevent the electrolyte from damaging the cathode material and can participate in the formation of a high-toughness CEI film with a high content of LiF and LiBxOy. In addition, the embodiment of the present application controls the mass percentage of the fluorophenylboric acid compound in the electrolyte to be 0.5% to 10%, so that the LiF and LiBxOy content in the generated CEI film can be reduced. x O y The content of LiF and LiB in the inner and outer layers of the cathode surface is distributed in a stepped manner. This is because the formation of the CEI film is not only affected by the film-forming time of the inner and outer layers, but also related to the content of fluorophenylboronic acid compounds. On the one hand, the film-forming stage includes the inner layer film-forming stage and the outer layer film-forming stage. In the film-forming stage, the CEI film is first generated in the inner layer of the cathode, and the inner layer film-forming time is relatively short. Therefore, the LiF and LiB in the generated CEI film are x O yThe content of LiF and LiB in the outer layer is relatively low; subsequently, as the chemical formation proceeds, the outer layer is continuously formed on the basis of the inner layer, and the outer layer takes a relatively long time to form, which will make the outer layer relative to the inner layer LiF and LiB x O y The content is higher, which results in the inner layer of LiF and LiB on the cathode surface. x O y The content of LiF and LiBxOy in the outer layer is small, and the content of LiF and LiBxOy in the outer layer is large. x O y A high content can prevent the inner CEI film from being damaged, improve the stability of the inner CEI, and thus increase the cycle life of the battery; on the other hand, if the content of fluorophenylboronic acid compounds is too low, they will be quickly consumed in the early stage of film formation (inner film formation stage), which may cause the LiF and LiB contained in the outer film to be x O y If the content of fluorophenylboric acid compounds is too high, the fluorophenylboric acid compounds at the cathode interface will be replenished too quickly, which may lead to excessive replenishment of fluorophenylboric acid compounds in the inner film-forming stage, which cannot be distinguished from the fluorophenylboric acid compounds replenished in the outer film-forming stage, making it difficult to form LiF and LiB in the CEI film. x O y Therefore, too high or too low a content is not conducive to the LiF and LiB x O y In addition, phenylboronic acid compounds can reduce the solvation effect between solvent and Li+, promote the desolvation effect of Li+, and improve the ion transfer rate.
[0040] As an optional embodiment, the structural formula of the fluorophenylboronic acid compound is as follows:
[0041]
[0042]
[0043] In structural formula 1, R1-R5 are each independently selected from one of C1-C10 alkanes, C1-C10 halogenated alkanes, fluorine atoms, cyano groups, and hydrogen atoms, and R1-R5 contain at least one fluorine atom; R6 and R7 are each independently selected from one of C1-C10 alkoxy groups, C1-C10 halogenated alkoxy groups, and hydroxy groups.
[0044] In the embodiment of the present application, R1, R2, R3, R4, and R5 can be selected from the same group or different groups, but at least one of R1, R2, R3, R4, and R5 is selected from a fluorine atom, so that the film-formed product contains LiF. R6 and R7 can also be selected from the same group or different groups.
[0045] As a preferred embodiment, the first additive comprises at least one of the following fluorophenylboronic acid compounds:
[0046]
[0047]
[0048] In the embodiments of the present application, compounds 1-4, 1-5 and 1-7 have better improvements on the high temperature cycle performance and high temperature storage performance of the battery, and compound 1-5 has the best performance improvement on the battery. This is because compound 1-5 contains more F atoms, and the molar ratio of F atoms is larger at the same content, which makes it easier to generate LiF that is beneficial to the CEI film.
[0049] As an optional embodiment, the electrolyte additive further includes a second additive, and the second additive includes a sultone compound.
[0050] The second additive of the embodiment of the present application includes a sultone compound, which is a sulfur compound that mainly participates in the construction of the SEI film at the stage of formation on the surface of the negative electrode to form sulfur compounds such as lithium alkyl sulfonate, which can prevent the continuous reduction and decomposition of the electrolyte on the surface of the negative electrode and provide a channel for the insertion and extraction of lithium ions. The first additive and the second additive have a synergistic effect. The first additive participates in the formation of the CEI film, inhibits the dissolution of the cathode transition metal, and reduces the content of Ni, Co, and Mn metal ions in the anode part. The second additive forms a stable interface film to block a small amount of transition metal from damaging the anode. The coordinated use of the two jointly improves the stability of the anode cycle process.
[0051] As a preferred embodiment, the structural formula of the sultone compound is as follows:
[0052]
[0053] In structural formula 2, R8 and R9 are independently selected from one of C1-C10 saturated alkanes, halogen atoms, and hydrogen atoms; M and Q are selected from C and O, respectively.
[0054] In the embodiment of the present application, R8 and R9 can be selected from the same group or different groups, and the present application does not limit this.
[0055] As a preferred embodiment, the second additive comprises at least one of the following sultone compounds:
[0056]
[0057]
[0058] Compound 2-5.
[0059] In the embodiments of the present application, compound 2-1, compound 2-2 and compound 2-4 work synergistically with compound 1-5 to achieve better improvements in the high temperature cycle performance and high temperature storage performance of the battery. Compound 2-1 works synergistically with compound 1-5 to achieve the best improvement in battery performance because compound 2-1 can facilitate the formation of a denser and more stable SEI film.
[0060] As an optional embodiment, the amount of the fluorophenylboronic acid compound and the sultone compound meets the following conditions:
[0061] 2(m 1 +m 2 )≥A
[0062] Among them, the molar ratio of Ni element in the positive electrode active material is A, and the mass percentage of sultone compound in the electrolyte is m 2 %.
[0063] In the present embodiment, the molar ratio A of the Ni element in the ternary positive electrode active material refers to the molar ratio of the Ni element. a C b M c , the molar ratio A of Ni element in the positive electrode active material is a.
[0064] The higher the Ni content in the positive electrode active material, the stronger the oxidizing property of the electrolyte, and the easier it is to oxidize the electrolyte. 1 +m 2 It indicates the synergistic effect of the fluorophenylboronic acid compound and the sultone compound in the first additive and the second additive. When 2(m 1 +m 2 )≥A, it means when m 1 、m 2 After the values of A are determined, the synergistic effect of the fluorophenylboric acid compounds and sultone compounds in the first additive and the second additive is not less than the oxidative effect of the Ni content on the electrolyte, and the electrolyte has a better protective effect on the positive electrode.
[0065] Preferably, A is 1-9.
[0066] In the embodiments of the present application, A can be 1, 3, 5, 6, 8, 9 or any value within the above-defined range, and the present application is not limited to this.
[0067] Preferably, m 2 It is 1 to 10.
[0068] In the present application embodiment, m 2It can be 1, 2, 5, 10 or any value within the above-defined range, and the present application does not impose any limitation on this.
[0069] If m 2 If m is too large, the impedance will deteriorate significantly and the cycle capacity will deteriorate. 2 If it is too small, it will lead to poor protection of the positive electrode.
[0070] Corresponding to the aforementioned application function realization method embodiment, the present application also provides an electrolyte, a lithium-ion battery and corresponding embodiments.
[0071] An embodiment of the present application provides an electrolyte, including a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive includes the aforementioned electrolyte additive.
[0072] In the embodiment of the present application, the lithium salt is selected from at least one of an organic lithium salt and an inorganic lithium salt.
[0073] Preferably, the lithium salt is selected from at least one of compounds containing fluorine and lithium.
[0074] Preferably, the lithium salt is selected from at least one of hexafluorophosphate, hexafluoroarsenate, perchlorate, trifluorosulfonyl lithium, difluoro(trifluoromethylsulfonyl)imide lithium, tris(trifluoromethylsulfonyl)methyl lithium, and bis(trifluoromethylsulfonyl)imide lithium.
[0075] Preferably, the lithium salt concentration is 0.5 M to 1.5 M. If the lithium salt concentration is too low, the conductivity of the electrolyte is low, which will affect the rate and cycle performance of the entire battery system; if the lithium salt concentration is too high, the viscosity of the electrolyte is too high, which will also affect the rate of the entire battery system.
[0076] More preferably, the concentration of the lithium salt is 0.8M to 1.3M.
[0077] Preferably, the non-aqueous organic solvent is selected from at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl formate, ethyl propionate, propyl propionate, methyl butyrate and tetrahydrofuran.
[0078] The additive further includes at least one of a sulfonate compound, a fluorocarbonate compound and a nitrile compound.
[0079] The embodiment of the present application also provides a lithium-ion battery, including a positive electrode, a negative electrode, a separator and an electrolyte, and the electrolyte is the aforementioned electrolyte.
[0080] In the embodiment of the present application, the positive electrode includes a positive electrode current collector and a positive electrode active slurry layer located on the positive electrode current collector, wherein the positive electrode active slurry layer includes a positive electrode active material; the negative electrode includes a negative electrode current collector and a negative electrode active slurry layer located on the negative electrode current collector, wherein the negative electrode active slurry layer includes a negative electrode active material. The specific types of the positive electrode active material, the positive electrode binder, and the negative electrode active material are not subject to specific restrictions and can be selected according to needs.
[0081] As an optional embodiment, the negative electrode active material can be selected from graphite and / or silicon, such as natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 , Li-Al alloys can be used as negative electrode active materials.
[0082] As an optional embodiment, the positive electrode active material of the positive electrode is selected from lithium cobalt oxide LiCoO 2 、Nickel manganese cobalt oxide lithium ternary material N a C b M c , LiFePO 4 , LiMn manganate 2 O 4 One or more of .
[0083] Preferably, the positive electrode active material is selected from the nickel manganese cobalt lithium ternary material N a C b M c , and the nickel manganese cobalt lithium ternary material N a C b M c Chinese: a+b+c=10.
[0084] Nickel manganese cobalt lithium ternary material N a C b M c For example, a+b+c=10, and the molar ratio A of the Ni element in the positive electrode active material is a.
[0085] More preferably, a / (b+c)>1.
[0086] For example, when a=8, b=1, c=1, a / (b+c)>1; when a=6, b=2, c=2, a / (b+b)>1; when a=5, b=2, c=3, a / (b+c)=1; when a=3.33, b=3.33, c=3.33, a / (b+c)<1.
[0087] In order to further understand the present invention, the present application is described below in conjunction with embodiments. These embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0088] 1. Preparation of batteries
[0089] (1) Preparation of electrolyte
[0090] EC / PC / EMC = 2 / 1 / 7 mass ratio was mixed as organic solvent. Add FEC additive to the organic solvent and mix well, then add LiPF 6 , and obtain LiPF 6 The mixed solution with a concentration of 1.1 mol / L was used as the electrolyte of Comparative Example 1 in Table 1, and the first additive and the second additive were added to the mixed solution according to the formula in Table 1 to prepare the electrolytes of various embodiments and comparative examples. Wherein, FEC is fluoroethylene carbonate.
[0091] (2) Production of positive electrode:
[0092] The nickel-cobalt-manganese ternary positive electrode active material, the conductive agent CNT, and the binder polyvinylidene fluoride are fully stirred and mixed in N-methylpyrrolidone solvent at a weight ratio of 97:1.5:1.5 to form a uniform positive electrode slurry. The slurry is coated on the positive electrode current collector Al foil, dried, and cold pressed to obtain a positive electrode sheet. Among them, the molar ratio of Ni in the nickel-cobalt-manganese ternary positive electrode active material is set according to Table 1.
[0093] (3) Production of negative electrode sheet:
[0094] The negative electrode active material graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector Cu foil, dried, and cold pressed to obtain a negative electrode sheet.
[0095] (4) Production of lithium-ion batteries:
[0096] Stack the positive electrode sheet, separator and negative electrode sheet in order, so that the separator is between the positive and negative electrodes to play an isolating role, and then wind it to the bare cell. Put the bare cell in the outer packaging bag, inject the electrolyte in Table 1 into the dried battery, and complete the preparation of the lithium-ion battery through vacuum packaging, static, formation, shaping and other processes.
[0097] Table 1 Recipe
[0098]
[0099]
[0100] 2. Performance Test
[0101] (1) High temperature cycle test of batteries
[0102] Test method: Place the battery in a 45±2 degree environment, follow the standard charge and discharge cycle, cycle rate 1C, charging voltage 3.0-4.3V, and calculate the capacity retention rate of the battery after the cycle. The calculation formula is as follows:
[0103] The nth cycle capacity retention rate (%) = (nth cycle discharge capacity) / (first cycle discharge capacity)*100%.
[0104] (2) High temperature storage test of batteries:
[0105] Test method: Charge the divided battery cells to 4.3V at room temperature with a current of 0.5C, place the fully charged battery in an environment of 85 degrees for 12 hours, measure the thickness expansion rate by heat, and after returning to room temperature, discharge the battery cells to 3.0V with a current of 0.5C and record the discharge capacity.
[0106] The battery test results are shown in Table 2.
[0107] Table 2 Test results
[0108]
[0109]
[0110]
[0111] Combining the data in Table 1 and Table 2, it can be seen from the data in Examples 1 to 14 that when the first additive is a fluorophenylboric acid compound and the second additive is a sultone compound, the high temperature cycle and high temperature storage performance of the battery can be improved; further combined with the data in Examples 15 to 18, and Comparative Examples 1 to 7, it can be seen that when m1 is 0.5 to 10 and m2 is 1 to 10, the high temperature cycle and high temperature storage performance of the battery can be effectively improved. Further combined with the data in Examples 20 to 23, and Comparative Example 8, it can be seen that when 2(m1+m2)-A≥0 is satisfied, the high temperature cycle and high temperature storage performance of the battery can be further effectively improved.
[0112] According to the data of Example 23, Comparative Examples 9 and 10, the selected nickel manganese cobalt lithium ternary material Na C b M c In the embodiment, when a / (b+c)>1 is satisfied, the high temperature cycle and high temperature storage performance of the battery can be effectively improved.
[0113] 3. ICP test of negative electrode
[0114] Example 5, Example 15 to Example 17, and Comparative Example 1 and Comparative Example 2 were selected to perform negative electrode sheet ICP test, and the test process was as follows:
[0115] First, discharge the cycled and stored battery cells to 3.0 V, disassemble the battery cells to remove the negative electrode sheets, scrape 0.2 g of the electrode sheet powder, and perform an ICP test after strong acid digestion. The test results are shown in Table 3.
[0116] Table 3 ICP test results of negative electrode
[0117]
[0118]
[0119] Further combined with the data in Table 3, it can be seen that the high-temperature cycling and high-temperature storage performance of Example 5 are the best, that is, the combination of 1% compound 1-5 and 5% additive 2-1 has the best effect, and under this combination, after high-temperature cycling and high-temperature storage, the dissolution level of transition metal ions in the positive electrode sheet is the lowest, and the protection effect on the positive electrode is the best.
[0120] Although the present application has been described with reference to preferred embodiments, it will be appreciated by those skilled in the art that various changes may be made and equivalents may be substituted for its elements without departing from the scope of the present application. In addition, many modifications may be made to adapt specific situations or materials to the teachings of the present application without departing from the substantive scope of the present application. Therefore, the present application is not intended to be limited to the specific embodiments disclosed as the best mode of implementing the present application contemplated, but the present application will include all embodiments falling within the scope of the appended claims.
[0121] All ranges disclosed in this application are inclusive of the endpoints, and the endpoints are combinable with each other.
[0122] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. An electrolyte additive, characterized in that: The invention comprises a first additive, wherein the first additive comprises a fluorophenylboric acid compound, and the mass percentage of the fluorophenylboric acid compound in the electrolyte is m1%, and m1 is 0.5-10.
2. The electrolyte additive according to claim 1, characterized in that: The structural formula of the fluorophenylboronic acid compound is as follows: In structural formula 1, R1-R5 are each independently selected from one of C1-C10 alkanes, C1-C10 halogenated alkanes, fluorine atoms, cyano groups, and hydrogen atoms, and R1-R5 contain at least one fluorine atom; R6 and R7 are each independently selected from one of C1-C10 alkoxy groups, C1-C10 halogenated alkoxy groups, and hydroxy groups.
3. The electrolyte additive according to claim 2, characterized in that: The first additive comprises at least one of the following fluorophenylboronic acid compounds:
4. The electrolyte additive according to claim 1, characterized in that: The electrolyte additive further includes a second additive, and the second additive includes a sultone compound.
5. The electrolyte additive according to claim 4, characterized in that: The structural formula of the sultone compound is as follows: In structural formula 2, R8 and R9 are independently selected from one of C1-C10 saturated alkanes, halogen atoms, and hydrogen atoms; M and Q are selected from C and O, respectively.
6. The electrolyte additive according to claim 5, characterized in that: The second additive comprises at least one of the following sultone compounds: Compound 2-5.
7. The electrolyte additive according to claim 4, characterized in that: The amounts of the fluorophenylboronic acid compound and the sultone compound satisfy: 2(m1+m2)≥A The molar ratio of Ni element in the positive electrode active material is A, and the mass percentage of sultone compound in the electrolyte is m2%; preferably, A is 1-9; and / or m2 is 1-10.
8. An electrolyte, characterized in that: The electrolyte comprises a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive comprises the electrolyte additive according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: A positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is the electrolyte according to claim 8.
10. The lithium ion battery according to claim 9, characterized in that: The positive electrode active material of the positive electrode is selected from lithium cobalt oxide LiCoO2, nickel manganese cobalt oxide lithium ternary material N a C b M c , lithium iron phosphate LiFePO4, manganese oxide LiMn2O4 or more; preferably, the positive electrode active material is selected from the ternary material N a C b M c , and the nickel manganese cobalt lithium ternary material N a C b M c In the embodiment of the present invention, a+b+c=10; further preferably, a / (b+c)>1.
Citation Information
Patent Citations
Electrolyte additive, electrolyte containing additive and lithium metal battery
CN116231081A
Electrolyte and lithium ion battery
CN117175014A
Lithium ion battery electrolyte and lithium ion battery containing same
CN117393856A
Lithium ion battery
WO2024045816A1